Comparison of Insulin Analogs and Human Insulins: A Narrative Review - Eledrisi, Mohsen S.; Danjuma, Mohammed Ibn-Mas'ud (Journal of Diabetes and Endocrine Practice, 2023)
Introduction Since insulin analogs have pharmacological properties that are similar to the normal physiological action of insulin, it has been suggested that they provide better glucose control and less rates of hypoglycemia compared to human insulins.Methods We performed a narrative, nonsystematic review of the literature including clinical trials, systematic reviews, meta-analyses, and professional guidelines related to the comparison of human insulins and insulin analogs in terms of glucose control, safety profile, and cost.Results Long-acting basal insulins result in mild improvement in glucose control and less rates of nocturnal hypoglycemic compared to neutral protamine Hagedorn insulin, mainly among patients with type 1 diabetes. Rapid-acting insulin analogs provide better glucose control and lower rates of hypoglycemia compared to regular insulin among patients with type 1 diabetes, whereas no advantage has been shown for insulin analogs among patients with type 2 diabetes for glucose control or hypoglycemia. Premixed insulin analogs provided no advantage in glucose control and inconsistent benefit in lowering the rates of hypoglycemia compared to human premixed insulins among patients with type 2 diabetes. The cost of insulin analogs is significantly higher than human insulins, and favorable cost-effectiveness has only been demonstrated for rapid-acting insulin analogs in type 1 diabetes.Conclusion Currently available evidence supports the use of rapid-acting insulin analogs and possibly long-acting basal insulin over human insulins for patients with type 1 diabetes. For patients with type 2 diabetes, the use of long-acting insulin analogs may be recommended for selected patients who are at an increased risk of significant hypoglycemia, while no clear benefits of meal insulin analogs over human insulins have been observed.
Keywords: diabetes mellitus; insulin analogs; human insulins